Homing peptides (rgd/irgd) functionalized zeolitic imidazolate framework-8 for targeted delivery of gemcitabine to lung cancer cell - Mohd Abdul Kamal, Nurul Akmarina (2022)
Lung cancer is a serious threat to human health, with metastasis being the top cause of cancer-related mortality. Gemcitabine (GEM) used in treating lung cancer operates in a non-selective manner tending to accumulate in normal tissue when cancer patients face a long duration of treatment. To mitigate the non-selective action of the GEM on the healthy tissues, there is a vital necessity to develop targeted nano delivery systems capable of regulating optimum doses selectively to cancer cells and minimizing untoward toxicity to normal tissues. Herein, a reticular nanoparticle zeolitic imidazolate framework-8 (nZIF-8) encapsulating GEM was surface-functionalized with selective homing systems (RGD; sequence Arg-Gly-Asp and iRGD; sequence Cys-Arg-Gly-Asp-Lys-Gly- Pro-Asp-Cys, respectively) through a straightforward, one-pot solvothermal reaction. Successful surface functionalization of nZIF-8 encapsulated GEM (GEM⊂nZIF-8) with RGD and iRGD, respectively, were characterized and systematically interpreted as a function of newly-formed functional groups, particle size, surface structure, surface topography, surface area, and surface charge. These functionalized GEMRGD@nZIF-8 and GEMiRGD@nZIF-8 not only responsive to an acidic environment but also controlled the GEM dissolution released rate (57.6 and 56.2%, respectively) after 48 h compared to nonfunctionalized GEM⊂nZIF-8 (76.0%). Both functionalized nanoparticles successfully increased the cellular uptake within cancerous human adenocarcinoma alveolar epithelial cells (A549), compared with nonfunctionalized nanoparticles. The highest uptake was shown by iRGD functionalized nZIF-8. The GEM⊂RGD@nZIF-8 and GEM⊂iRGD@nZIF-8 experienced not only efficient uptake within A549, but also induced obvious cytotoxicity (75 and 73%, respectively at 10 μg mL−1) and apoptosis (62 and 74.9%) post 48 h treatment when compared to the GEM⊂nZIF-8. The apoptosis study verified the ability of functionalized GEM⊂iRGD@nZIF-8 to intensify the apoptotic population in A549 while minimizing cell death (11%) in normal human lung fibroblast cells (MRC-5). Both functionalized nanoparticles reflect a potential outstanding treatment efficacy when GEM⊂RGD@nZIF-8 and GEM⊂iRGD@nZIF-8 demonstrated selective cytotoxicity (selective index, SI > 2) towards A549 than MRC-5. The follow-up study using healthy zebrafish embryos demonstrated enhanced permeation by both functionalized nanoparticles. At the lethal endpoint (96 h), all nanoparticles at all concentrations (7.81-250 μg mL-1) did not elicit toxicity during embryonic and larvae stages. With the absence of nZIF-8, pristine GEM at a concentration of 250 μg mL-1 exhibited 33% of pericardially and yolk sac edema indicating adverse side effects of the chemotherapeutic agent alone towards healthy tissue. Taken together, it is believed that surface functionalization of zeolitic imidazolate framework-8 with RGD/iRGD holds great selective targeting and enhances the optimum chemotherapeutic dosage to human lung cancer with less unwarranted toxicity to normal human lung fibroblast.